Family History of Psychiatric Disorders and Clinical Factors Associated With a Schizophrenia Diagnosis - Lina Díaz-Castro MD, PhD; Kurt Hoffman PhD; Héctor Cabello-Rangel MD, PhD; Armando Arredondo MD, PhD; Miguel Ángel Herrera-Estrella MD (SAGE Publishing, 2021)
Background Schizophrenia (SCH) and bipolar disorder (BD) have both shared and unique genetic risk factors and clinical characteristics. The aim of the present study was to identify potential risk factors significantly associated with SCH, relative to a BD reference group. Methods Data were obtained from medical records of patients that entered a major Mexico City hospital during 2009-2010 presenting psychotic symptoms (n = 1132; 830 cases of SCH, 302 cases of BD; 714 men and 418 women). SCH and BD diagnoses were compared with respect to a number of family and clinical characteristics. Logistic and linear regression analyses were used to respectively identify factors selectively associated with the SCH diagnosis relative to the BD diagnosis and explore the relationship between PANSS scores and parental age at time of birth to the age of SCH onset. Results Patients with SCH showed greater functional impairment than those with BD. Family history of mental illness, premorbid schizoid-like personality, and obstetric trauma were significantly associated with the SCH diagnosis. The association of obstetric trauma with SCH was greatest in male patients with a family history of mental illness. In women, increased paternal and decreased maternal age at time of the patient's birth were associated with an earlier age of SCH onset. Conclusion Male gender, showing premorbid schizoid-like personality, familial SCH, and obstetric trauma are risk factors that distinguish SCH from BD. Additionally, our results suggest that risk for SCH relative to BD may be importantly influenced by interactions between familial risk, gender, and obstetric trauma.